2019
DOI: 10.3126/jdean.v3i1.24072
|View full text |Cite
|
Sign up to set email alerts
|

National Consensus Statement on the Management of Type 2 Diabetes Mellitus in Nepal

Abstract: The full National Consensus Statement on the Management of Type 2 Diabetes Mellitus in Nepal is included here.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…However, international guidelines are well established but are missing in the implementation of health care facilities of Nepal. 40 Therefore, the present study provides useful insights for policy makers and health care providers with regard to the future resource use and costs to manage T2D. However, more evidence is needed to obtain a broader picture of the direct and indirect cost of health care resource use among diabetes patients in the wider community.…”
Section: Discussionmentioning
confidence: 91%
“…However, international guidelines are well established but are missing in the implementation of health care facilities of Nepal. 40 Therefore, the present study provides useful insights for policy makers and health care providers with regard to the future resource use and costs to manage T2D. However, more evidence is needed to obtain a broader picture of the direct and indirect cost of health care resource use among diabetes patients in the wider community.…”
Section: Discussionmentioning
confidence: 91%
“…If the goals are unmet, the therapy should be escalated to next phase and/or insulin should be added or intensified as required b ADA/EASD [60]In dual therapy along with metforminIn triple therapy along with metformin and SU, TZD or insulinIn combination injectable therapy with metformin and basal insulinNon-insulin antidiabetic pharmacotherapy in patients with established CVD: a position paper of the European Society of Cardiology Working Group on Cardiovascular Pharmacotherapy [61]A few SGLT2i (empagliflozin and canagliflozin) and GLP-1 RAs (liraglutide and semaglutide) reduced CV events in adequately powered studies with contemporary concomitant CV treatment in patients with established CVD (mainly stable CHD with the exclusion of recent ACS) and hence may be considered as the preferred treatment choiceWhen the aforementioned preferred treatments (with selected SGLT2i and GLP-1 RA) are not sufficient to achieve therapeutic goals or are contraindicated, agents such as thiazolidinedione-pioglitazone, GLP1 RA-exenatide and dipeptidyl peptidase inhibitors which have established neutral or potentially beneficial effects on CV events in adequately powered, contemporary trials may be preferredAntidiabetic pharmacotherapy should be chosen on the basis of beneficial effects on CV events in phase 3 and post-marketing trials and as per EMA; improvement of glycaemic control and reduction of CV morbidity and mortality should be major goals in the treatment of T2DMIDF [62]In dual therapy if weight loss is a priority and if the drug is affordableIn triple therapy instead of basal insulin along with 2 glucose-lowering drugs if weight loss has been insufficientPatients should not remain longer than 3 to 6 months with HbA1c above target before adding a second glucose-lowering drugNICE [63]In combination with metformin and SU if triple therapy with metformin and 2 other OADs is not effective, not tolerated or contraindicatedContinued only if the person with T2DM has had a beneficial metabolic response (a reduction of at least 1% in HbA1c and a weight loss of at least 3% of initial body weight in 6 months)In combination with insulin, only with specialist care advice and ongoing support from a consultant-led multidisciplinary teamRSSDI [64]As an add-on to metformin in obese T2DM patients in addition to lifestyle changesAs second-line or third-line option for the management of uncontrolled hyperglycaemiaAs second-line therapy in overweight/obese patients with metformin inadequacy and as first-line therapy in patients with metformin intoleranceAs an add-on to insulin therapy if glycaemic goals are unmet with reasonably high doses of insulin or if unacceptable weight gain or hypoglycaemia occursGLP-1 RAs with proven CV benefit, e.g. liraglutide, should be considered to reduce the risk of major adverse CV eventsDEAN [65]As a third-line agent to metformin (+ lifestyle modification) and SU/DPP4 inhibitor/α-glucosidase inhibitor if glycaemic target is not achieved in 2 months…”
Section: Overview Of Glp-1 Ra Recommendations For T2dm Management Fromentioning
confidence: 99%
“…Hypothyroidism is more common among thyroid disorders with a female preponderance. 2,3 Studies have suggested a strong association between hypothyroidism and low vitamin D levels. [4][5][6] Given that both thyroid hormones and vitamin D bind to the same family of steroid/nuclear hormone receptors and share similar response elements on gene promoters, it is highly likely that thyroid hormones and vitamin D might be intricately linked.…”
Section: Introductionmentioning
confidence: 99%